Uptake rates of ammonium and nitrate by phytoplankton communities in two eutrophic tropical reservoirs. Issue 5 (9th October 2017) - Gasparini Fernandes Cunha, Davi; Fernandes de Melo Lima, Vitória; Menegante Néri, Amanda; Albino Marafão, Gabriela; Cristina Poli Miwa, Adriana; do Carmo Calijuri, Maria; Albertino Bendassoli, José; Tromboni, Flavia; Maranger, Roxane
Abstract : While excess phosphorus typically results in the eutrophication of inland waters, there is growing evidence that excess nitrogen (N) and the availability of different N forms influence phytoplankton community composition, often favoring potentially toxic genera. In this study, the environmental dynamics, phytoplankton community structure, and N uptake rates were investigated in two tropical reservoirs. Phytoplankton ammonium ( N H 4 + ) and nitrate ( N O 3 − ) acquisition was assessed through 15 N addition experiments over 2 years. We found that changes in ambient nutrient concentrations and temperature influenced different phytoplankton groups, which tended to have different N uptake strategies. The preferred N‐source by Cyanobacteria was N H 4 + while Dinophyceae and other groups seemed adapted to also take up N O 3 −, possibly due to competition. Potential uptake rates (maximum of 8.5 μM‐N hr −1 for N H 4 + and 1.3 μM‐N hr −1 for N O 3 − ) were high in comparison to previous reports from temperate freshwater or marine systems, likely due to elevated algal biomass and temperature. When normalized to biomass as chlorophyll‐a (Chl‐a), specific uptake rates varied between 0.01–3.4 μmol‐N μgChl‐a −1 day −1 for N H 4 + and <0.01–0.8 μmol‐N μgChl‐a −1 day −1 for N O 3 − and were comparable to those reported for other eutrophic and hypereutrophic aquatic systems. In addition, higher temperatures favored Cyanobacteria (e.g., Cylindrospermopsis raciborskii and Microcystis aeruginosa ), while a more diverse community was found during colder months. Results highlight how high loading of reduced forms of nitrogen and high temperatures can exacerbate harmful Cyanobacteria blooms in tropical reservoirs and be a concern for drinking water quality.